Solvabilidade de soluções via Nagumo e Osgood para o problema x0 = f(t; x) - PORTUGAL, Izaque Pantoja (2019)
This work appeared of the result of the scientific initiation research of the book of renowned Dro Luiz Adauto da Justa Medeiros about Ordinary Differential Equations, because in his book he makes a qualitative study of the differential equation to climb x0 = f(t; x), specifically will approach the study of uniqueness of solutions of a differential equation of first order of a qualitative point of view. For such we will exhibit the solution definitions, and we will make a basic study of metric spaces, with focus in complete metric spaces and the sequences of Cauchy. We showed a little of the history of Mathematicians Willian Foog Osgood and Mitio Nagumo and we exhibited their conditions of uniqueness for the solution of the problem x0 = f(t; x)